Projeto de um demultiplexador de cristal fotônico bidimensional baseado em grafeno para aplicação em sistemas por divisão de comprimento de onda (WDM). - SILVA, Alan dos Reis (Universidade Federal do Pará, 2025)
This work presents an eight-channel 2D photonic crystal demultiplexer based on graphene for application in optical systems that use the wavelength division multiplexing technique - WDM. The optical device was designed based on a square crystalline lattice of silicon dielectric rods immersed in air and is formed by three main parts: Bus waveguide; Octagonal resonator rings and L-curve waveguides. The COMSOL multiphysics software and the Legumes python packages were used to study and simulate the designed structure. In analyzing the simulation results, the resonant wavelength, spectral width, quality factor, transmission efficiency, spacing between channels and the level of electromagnetic interference (Crosstalk) for the eight channels of the demultiplexer were evaluated. Furthermore, the analysis of the results occurred from two different perspectives, in the first of which the relationship between the transmission parameters of the demultiplexer with the variation in the chemical potential of graphene was analyzed and in the second the application of the device in WDM systems was explored. In general, the analyzes carried out proved to be considerable regarding the application of the photonic device in optical wavelength division multiplexing (WDM) systems.